2015
DOI: 10.1108/mip-12-2013-0201
|View full text |Cite
|
Sign up to set email alerts
|

Green segmentation: a cross-national study

Abstract: Purpose – Understanding and defining the characteristics of environmentally conscious or concerned consumers has received attention from academic researchers, commercial sector, and policy makers. The purpose of this paper is to identify distinct market segments in three countries (China, Germany, and Turkey) based on several “green” attitude and behavior variables. Design/methodology/approach – A survey was administered in three countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…(b) Individual well‐being has had a great influence on the purchasing attitude of green products (Dagher et al, ; Johnstone & Tan, ; Lai & Cheng, ). Environment‐friendly consumption patterns will also contribute to an individual's well‐being (Chaudhuri, Giffi, Kandaswami, & Singh, ; Yilmazsoy, Schmidbauer, & Rösch, ). A quarter of the United Kingdom and ZERO of Indian consumers said they would be willing to pay the green premium (Johnston & Tan, 2015; Peattie, ; Yadav & Pathak, ).…”
Section: Conclusion and Applicationmentioning
confidence: 99%
“…(b) Individual well‐being has had a great influence on the purchasing attitude of green products (Dagher et al, ; Johnstone & Tan, ; Lai & Cheng, ). Environment‐friendly consumption patterns will also contribute to an individual's well‐being (Chaudhuri, Giffi, Kandaswami, & Singh, ; Yilmazsoy, Schmidbauer, & Rösch, ). A quarter of the United Kingdom and ZERO of Indian consumers said they would be willing to pay the green premium (Johnston & Tan, 2015; Peattie, ; Yadav & Pathak, ).…”
Section: Conclusion and Applicationmentioning
confidence: 99%
“…Several studies have observed lifestyles as psychographic variables that give a clearer orientation to companies for identifying the ecological consumer segment Martinez, 2006a, 2006b;Rios et al, 2006;Chan et al, 2006;Pickett-Baker and Ozaki, 2008;Khare, 2014). Notably, studies on green consumer behavior have been generating considerable interest as of late (Lao, 2014;Mohd Suki and Mohd Suki, 2015;Yilmazsoy et al, 2015;Moser, 2015;Aagerup et al, 2016;Bailey et al, 2016;Swaim et al, 2016;Onel and Mukherjee, 2016;Ko and Jin, 2017;Sony and Ferguson, 2017). For more than a decade, marketers have called for additional research regarding the predictors of sustainable consumption because it is often difficult to encourage this type of consumer behavior (Do Paco and Raposo, 2009;Yeon Kim and Chung, 2011;Chen, 2014).…”
Section: The Question Ismentioning
confidence: 99%
“…Studies over the past decade have attempted to segment the green market in terms of various segmentation variables by subdividing them into potential target segments such as environmental knowledge, values, concern, attitudes, and behavior (do Paço et al, 2009;Elgaaied, 2012;Oliver and Rosen, 2010;Yilmazsoy et al, 2015). The evidence establishes that researchers identify the segmentation variables in line with the research objectives, as suggested by Hair et al (2010).…”
Section: Green Segmentationmentioning
confidence: 93%
“…Interestingly, in segmentation studies, there is a notable paucity of empirical research focusing on environmental attitudes as a segmentation variable. A recent study of Yilmazsoy et al (2015) successfully separates consumer segments based on the respondents' environmental attitudes across China, Germany, and Turkey.…”
Section: Environmental Attitudes and Purchase Intentionsmentioning
confidence: 99%
See 1 more Smart Citation